I think the answer is B im not sure :(
Let's
simplify step-by-step.
3x2(x2−4x−4)+5x3+7x2+2x+11
Distribute:
=(3x2)(x2)+(3x2)(−4x)+(3x2)(−4)+5x3+7x2+2x+11
=3x4+−12x3+−12x2+5x3+7x2+2x+11
Combine
Like Terms:
=3x4+−12x3+−12x2+5x3+7x2+2x+11
=(3x4)+(−12x3+5x3)+(−12x2+7x2)+(2x)+(11)
=3x4+−7x3+−5x2+2x+11
Answer:
=3x4−7x3−5x2+2x+11
<span> </span>
Answer:
The answer to your question is:
Step-by-step explanation:
x² + 3x - 5
x² + 3x + (3/2)² = 5 + (3/2)²
(x + 3/2)² = 5 + 9/4
(x + 3/2)² = (20 + 9) /4
(x + 3/2)² = 29/4
x + 3/2 = ±√29 / 2
x 1 = -3/2 + √29/2 x2 = -3/2 - √29/2
x1 = 1.19 x2 = -4.19
96,910. Is that what you were looking for?